2012
DOI: 10.1530/erc-12-0203
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular mechanisms by which insulin influences breast cancer risk and progression

Abstract: Epidemiological studies have related hyperinsulinemia and type 2 diabetes to an increased breast cancer risk, an aggressive and metastatic phenotype, and a poor prognosis. Furthermore, diabetic retinopathy arises from pathological angiogenesis, which is also essential for breast cancer growth and metastasis. Insulin stimulates the proliferation of some human breast cancer cell lines in vitro by mechanisms that use both the phosphatidylinositol-3 kinase and the mitogen-activated protein kinase/Akt signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 120 publications
5
128
2
4
Order By: Relevance
“…In accordance with this, previous experimental and epidemiological studies have demonstrated a positive correlation between insulin levels and cancer development (Belfiore & Malaguarnera 2011). As regards breast cancer, the potential of insulin to contribute to tumor progression has been highlighted in diverse investigations (Rose & Vona-Davis 2012, Sieri et al 2012, Catsburg et al 2014. Nicely supporting these data, in postmenopausal women within the framework of the Women's Health Initiative Observational Study (WHI-OS), the highest tertile of baseline insulin was associated with a twofold risk increase in breast cancer compared with the lowest tertile (Kabat et al 2009).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In accordance with this, previous experimental and epidemiological studies have demonstrated a positive correlation between insulin levels and cancer development (Belfiore & Malaguarnera 2011). As regards breast cancer, the potential of insulin to contribute to tumor progression has been highlighted in diverse investigations (Rose & Vona-Davis 2012, Sieri et al 2012, Catsburg et al 2014. Nicely supporting these data, in postmenopausal women within the framework of the Women's Health Initiative Observational Study (WHI-OS), the highest tertile of baseline insulin was associated with a twofold risk increase in breast cancer compared with the lowest tertile (Kabat et al 2009).…”
Section: Discussionsupporting
confidence: 63%
“…In particular, high insulin levels are associated with an augmented risk of breast cancer and breast cancer relapses in diabetic and nondiabetic women (Duggan et al 2011, Cohen & Le Roith 2012, Sieri et al 2012. It has been well established that a cooperative crosstalk between insulin and estrogen signaling pathways triggers multiple biological events in breast carcinogenesis (Rose & Vona-Davis 2012, Catsburg et al 2014. Estrogens mainly act through the classical estrogen receptor a (ESR1) and b (ESR2) (Hall et al 2001), however many effects induced by these steroids are mediated by the G protein estrogen receptor 1 (GPER1, formerly known as GPR30) in several types of tumor cells and cancer-associated fibroblasts (CAFs), major players in the tumor microenvironment driving tumor progression (Madeo & Maggiolini 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The major findings of our study were a significant association between pretreatment insulin levels and advanced disease stage, translating to a positive association of HOMA index, and the demonstration that pretreatment insulin levels (HR: 2.2) and HOMA index (HR: 1.91; 95% CI: 1.06-3.42) (data not shown) might act as negative prognostic factors for PFS, independently of other well-established prognostic factors (i.e., stage, hormone receptors, HER2/neu and Ki67 expression). Indeed, patients with insulin levels above a cutoff of 13 mIU/mL had a twofold increased risk for disease progression (5-year survival rate: 55%) compared with patients with insulin levels below this cutoff (5-yearsurvivalrate:85%),corroboratingtheexperimentalfindings of an insulin role in tumor growth and metastasis either directly, by stimulation ofcell proliferation and/or inhibition of apoptosis [2,13], or indirectly through the elevation of endogenous sex steroid hormones caused by insulin-mediated reduction of hepatic sex hormone-binding globulin [6].…”
Section: Discussionsupporting
confidence: 74%
“…Hyperinsulinemia, insulin resistance (IR) [7,8,10], and enhanced levels of insulin-like growth factor-1 (IGF-1) [11] have all been proposed as the underlying causative mechanisms, mainly on the basis of in vitro and animal studies supporting a role for insulin, insulin receptor, and IGFs in BC initiation [12][13][14] and progression [15]. These experimental findings are strengthened by indirect observations that metformin, a biguanide oral hypoglycemic agent capable of lowering insulin levels and improving IR, also might The Oncologist 2016;21:1041-1049 www.TheOncologist.com ©AlphaMed Press 2016 be effective in reducing BC incidence [8] and may beneficially act on proliferation and apoptosis markers in early BC stages [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Le lecteur intéressé par cet aspect de l'interaction entre tissu adipeux et cancer peut se référer à la revue de Park et al [33]. De plus, bien que l'effet pro-invasif des adipocytes péritumo-raux soit indépendant de l'expression du récepteur des oestrogènes, la production d'oestrogènes par les adipocytes (via leur capacité d'aromatisation des androgènes) est susceptible de favoriser la prolifération de certaines tumeurs RE + et participe certainement à l'initiation tumorale dans le cas des cancers du sein survenant après la ménopause [34]. Enfin, d'autres composants du tissu adipeux, et en particulier les ADSC, contribuent à la progression tumorale, ce qui renforce l'importance de l'ensemble des composants de ce tissu en cancérologie [8].…”
Section: Le Tissu Adipeux Ou Plutôt Les Tissus Adipeux : De L'importaunclassified